The Diversity of Islamic Javanese Kings’ Waqf Management: Ruislag and Various Social Conflicts - Zaenurrosyid, A; Sholihah, Hidayatus; Miftahuddin, Miftahuddin; Nawawi, Nawawi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
The main benefit of waqf (endowment) assets is fundamentally for the welfare of the community. However, various conflicts often occur within waqf management, such as among nāẓir (waqf managers) and bureaucrats, including that on waqf ruislag (ibdāl) in Kendal, Semarang, and Demak affected by the national road project. Taking the cases as a sample, this research aims to explore various management and utilization of waqf assets, to examine diversity in land exchange involving waqf lands from Javanese kings, and to uncover various conflicts in management and exchange of waqf assets. This study employs a socio-anthropological approach with qualitative analysis. Data were collected through interviews with nāẓir, officials from the Ministry of Religious Affairs, and engaging foundation's staff. Additionally, the research involved reviewing waqf asset records, examining documents, and conducting necessary observations. The findings of this study are: First, a wide variety of waqf assets are managed in different forms, serving various purposes such as education, healthcare, and other social benefits services. Second, as some waqf assets have been impacted by the national road project, ibdāl waqf, when considered for maṣlaḥah ‘āmmah (public benefit), took place under consideration that a particular Islamic law school and Law No. 4 of 2004 allowed it. Third, the ibdāl has given rise to various conflicts involving waqf institutions, foundations, or legal entities. Therefore, conflict prevention is very important for waqf asset governance based on nāẓir collective awareness, regulations, and resolution.